Venous thromboembolism in amyotrophic lateral sclerosis: a prospective study - Gladman, Matthew; Dehaan, Melanie; Pinto, Hanika; Geerts, William; Zinman, Lorne (Neurology, 2014)
To prospectively assess the incidence of both symptomatic and asymptomatic venous thromboembolism (VTE) in patients with amyotrophic lateral sclerosis (ALS) and to identify risk factors. Fifty outpatients with ALS were recruited consecutively and prospectively evaluated with bilateral venous duplex ultrasonography (VDU) of the proximal leg veins at enrollment and 6 and 12 months. The primary outcome measure was clinically important VTE, defined as asymptomatic proximal deep vein thrombosis (DVT) by screening VDU, symptomatically proven DVT or pulmonary embolism (PE), or fatal PE. For each patient, person-days of follow-up were recorded from enrollment until the date of VTE, death, loss to follow-up, or final 12-month visit. During the 1-year follow-up period, VTE was detected in 4 patients (1 symptomatic DVT, 1 symptomatic PE, and 2 asymptomatic DVTs) over 13,011 person-days of follow-up, representing an 11.2% 1-year incidence. Subjects with leg-onset ALS or significant leg weakness had a 1-year VTE incidence rate of 35.8% and 35.5%, respectively. VTE risk was significantly increased for those patients with decreased lower extremity Revised ALS Functional Rating Scale subscore (p = 0.03), decreased Lower Extremity Activity Scale score (p = 0.02), and decreased average lower limb Medical Research Council scale strength score (p = 0.03). Our data suggest that clinically important VTE is common in patients with ALS, particularly those with leg weakness and reduced mobility. Given these results, the potential benefits of routine VTE screening and primary prophylaxis in high-risk patients with ALS with leg weakness should be explored in future studies. In the meantime, physicians should have a low threshold for considering VTE in patients with ALS with leg weakness.